Feminist Perspective On Animated Films: A Study To Examine The Change In Portrayal Of Female Leads - Jasrotia, Shailmadhur; NavsangeetSaini, (The journal of contemporary issues in business and government, 2021)
Animated Films have been applauded and have garnered much fan following and acclaim owing to their creativity. The stories in the films tend to have a lasting impact on the minds of the audience and have influenced generations to take inspiration from the characters and stories. The stories have effected traditions, cultural values and gender norms across societies. It is in the wake of the huge impact that these films tend to exercise on the minds of the audience especially the impressionable children, thereby shaping their moral and value systems, that the films are often subjected to a lot of scrutiny in their role in the lives of the audience and their effect on their thought processes. These films, especially from the yesteryears, have been ridiculed for their glorification of male machismo and portrayal of female lead as a damsel in distress that requires saving by the hero of the film. Also the cliched depiction of beauty standards is another factor that adds to the ridicule. This study examines the popular animated films from Hollywood and studies the depiction of the female lead in the films. The study finds that there has been a lot of difference in how the female lead was depicted in old times and the female lead in the animated films in recent years. This signals a paradigm shift in the way women are represented in films and kind of influence they have on the societal values.